2018
DOI: 10.1002/ajb2.1150
|View full text |Cite
|
Sign up to set email alerts
|

First genome‐wide analysis of the endangered, endemic lichen Cetradonia linearis reveals isolation by distance and strong population structure

Abstract: Our findings contribute to the understanding of factors that shape genetic diversity in C. linearis and in fungi more broadly. Because all populations are highly genetically differentiated, the extirpation of any population would mean the loss of unique genetic diversity; therefore, our results support the continued conservation of this species.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 87 publications
3
21
0
Order By: Relevance
“…This is mainly due to (i) the complexity of the lichen thalli-beside the two major symbionts, lichens host also additional fungi (yeast and filamentous fungi as parasites or cryptic endolichenic) algae and bacteria [112][113][114], (ii) the impossibility (still) to reproduce and maintain in culture a whole lichen symbiosis, and (iii) the particularly challenging isolation of the lichen mycobionts, which requires lots of attempts and it can take up long time (from several months up to one year) before obtaining enough fungal mycelium to be used for experiments and/or sequencing. Nevertheless, studies demonstrated that it is possible to gain relatively complete genome data for lichen mycobionts bypassing aposymbiontic isolation in culture [115,116]. A list of all reviewed genomic works concerning licghen symbioses is shown in Appendix A.…”
Section: Lichenized Fungimentioning
confidence: 99%
“…This is mainly due to (i) the complexity of the lichen thalli-beside the two major symbionts, lichens host also additional fungi (yeast and filamentous fungi as parasites or cryptic endolichenic) algae and bacteria [112][113][114], (ii) the impossibility (still) to reproduce and maintain in culture a whole lichen symbiosis, and (iii) the particularly challenging isolation of the lichen mycobionts, which requires lots of attempts and it can take up long time (from several months up to one year) before obtaining enough fungal mycelium to be used for experiments and/or sequencing. Nevertheless, studies demonstrated that it is possible to gain relatively complete genome data for lichen mycobionts bypassing aposymbiontic isolation in culture [115,116]. A list of all reviewed genomic works concerning licghen symbioses is shown in Appendix A.…”
Section: Lichenized Fungimentioning
confidence: 99%
“…Comparative population genetic data on lichens from glacial refugia and formerly glaciated areas are scarce and entirely lacking for Antarctic lichens, but higher genetic diversity and numbers of private alleles in glacial refugia and gradual decrease of diversity with increasing distance from these areas have been observed in some Northern Hemispheric species (Allen et al, 2018; Printzen et al, 2003; Scheidegger et al, 2012). The lower diversity levels on the Falkland Islands and in Chile north of Navarino Island as well as on Elephant and Deception Island might therefore characterise these populations as more recently colonised from refugial populations on both sides of the Drake Passage.…”
Section: Discussionmentioning
confidence: 99%
“…However, bioclimatic modelling of lichens has been used for a wide variety of purposes, and many such studies have explored the relationship of lichen distribution to baseline climate only, alongside a range of other covariables, and without projection to climate change scenarios (Table 1). Thus, lichen bioclimatic modelling has been used to test taxonomic hypotheses [32][33][34][35][36], improve understanding of threatened species [37][38][39][40][41][42][43][44][45] including through conservation design [46,47], identify indicator species [48][49][50][51], or to test and improve the practical application of bioclimatic methods [37,[52][53][54]. These studies at the baseline highlight three key interrelated decisions characterising the development process for any bioclimatic model: 1.…”
Section: Bioclimatic Analysis Of Lichensmentioning
confidence: 99%
“…Lichen distributions are dynamic [55] and any shifts within this baseline period are discounted; there is an important balance to be struck between a time period that extends to provide a reliable distribution, minimising issues of spatial bias [56,57], while constraining this period to represent as stable a distribution as is possible with respect to prevailing climate. Furthermore, field occurrence records provide 'presence-only' data which present an additional statistical challenge that has been handled along a continuum, as follows: (i) by generating a constrained set of pseudo-absences [58,59] for use with standard forms of regression such as generalised linear or additive models [33,39] or with alternative methods that facilitate nested interactions such as classification and regression trees including random forest [33], (ii) using a controlled selection of 'background' pseudo-absence points as applied in MAXENT [34,35,40,[43][44][45], or alternatively (iii) using presence-only statistical methods that compare occurrences to the properties of an entire environmental 'background' [38,46,47]. Lichen bioclimatic models have thus used a rich variety of statistical techniques (Table 1), extending to include nonparametric multiplicative regression that has been applied to >50% of studies with abundance or presence-absence data [36,48,50,51].…”
Section: Bioclimatic Analysis Of Lichensmentioning
confidence: 99%
See 1 more Smart Citation